PENGARUH E_PRODUCT QUALITY, E_SERVICE QUALITY, E_INNOVATION, E_PRICE DAN E_STORE IMAGE TERHADAP E_PURCHASE INTENTION SOCIOLLA - Lestari, Ririn Ari Dwi; Dewi, Citra Kusuma (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2021)
E-commerce (electronic commerce) is currently being loved by online shopping lovers. In simple terms, e-commerce can be explained as the process of buying and selling products electronically. Due to the development of e-commerce in recent years, e-commerce can gradually replace traditional or offline stores. Sampling was done by non-probability sampling method, namely by purposive sampling technique. The sample used in this study were 100 respondents. The analytical method used in this study is the Multiple Regression Analysis test and the analytical tool used with the help of SPSS version 25. The results of the coefficient of determination test obtained a value of 95.8%. This means that the relationship between the independent variable and the dependent variable is 95.8%. e_product quality there is no effect between e_product quality on e_purchase intention partially. e_service quality there is an effect between e_service quality on e_purchase intention. e_innovation there is no effect between e_innovation on e_purchase intention partially. e_price there is no effect between e_price on e_purchase intention partially. There is no partial effect of e_store image on e_purchase intention. The effect of E_Product Quality, E_Service Quality, E_Innovation, E_Price and E_Store Image on E_Purchase Intention simultaneously on Sociolla, based on the results of the f test on the variables e_product quality, e_service quality, e_innovation, e_price and e_store image on e_purchase intention obtained f count of 195.047 with a probability of 0.000 whose value is below 0.05. which means that there is an effect of e_product quality, e_service quality, e_innovation, e_price and e_store image on e_purchase intention. Keywords: e_product quality, e_service quality, e_innovation, e_price, e_store image, e_purchase intention